Assessment and Management of Dehydration in Children Based on Digital: A Systematic Review - Wea, Lidwina Dewiyanti; Dewi, Yulis Setiya; Efendi, Ferry (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2024)
Dehydration remains a critical issue in children and can pose a risk of mortality. Nurses play a crucial role in promptly and accurately preventing dehydration, beginning with the recognition of its causes and symptoms in patients. A thorough assessment by nurses is key to ensuring proper and timely treatment of dehydrated patients, especially in high-activity emergency units. The integration of technology into emergency units is essential for enhancing patient services and decision-making processes. This study aims to conduct a systematic review by analyzing the use of mobile phone applications in assessing signs of dehydration and possible management in hospital services. Four databases (Scopus, Science Direct, and Pubmed) were used in this study using the keywords assessment, smartphone, and dehydration management. Access to the quality of this study using a cross-sectional design from Joanna Briggs Institute. Use the PRISMA flowchart to summarize the study selection. Limit for the last eight years, namely 2017 – 2022. The results of this study met the inclusion criteria, including patients with dehydration caused by gastroenteritis problems and pediatric or pediatric patients. inclusion and exclusion criteria applied to the PICOS framework. The result of eleven studies in the article found that a digital-based dehydration management approach is very beneficial for the effectiveness of services and initial assessment of the patient's clinical condition. The integrity of digital technology in healthcare has revolutionized many aspects of healthcare management and delivery. By implementing digital solutions such as dehydration management documents, health workers can improve their ability to prevent and treat dehydration.